7 - LE PROBLEME DE LA REFORME AGRAIRE EN AFRIQUE AU SUD DU SAHARA - M. L. GAKOU, (Africa Development, 1979)
In This short article, we have tried to point out a few of the crucial issues faced when dealing with the problem of agricultural reform in Africa South of Sahara. The analysis is limited to this area simply because the problems of land tenure are more or less the same although different enough from what could be noticed in North Africa. In most of the countries in Africa South of Sahara, the res trictions to land property are comparatively reduced since the relation between man and land is favourable in most cases. The land tenures inherited from the colonial system have been slightly modified. They allow the coexistence of western land and traditional customary law, private property and collective property of land. Here the problem agricultural reform is not so much a more equitable distribution of but rather a question of the rationalisation of the use of land to avoid deterioration of soils and ecological imbalance. Naturally this rationali sation begins with the fight against water shortage and the evolution towards a more intensive agriculture. To achieve this, it is essential most of the surplus yielded by agriculture is reinvested in it. The reorga nization of the agricultural sector would be made easier by bringing scattered peasants together. This could lead to a more efficient utiliza tion of investments made by the state and those that are collectively carried out by the peasants. From this point of view, the « Ujamaa Villages » experience in Tanzania is very v